2021
DOI: 10.53682/edutik.v1i3.1546
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Model Pembelajaran Blended Learning Untuk Meningkatkan Hasil Belajar Siswa SMK

Abstract: Pendidikan adalah usaha sadar untuk menyiapkan peserta didik melalui kegiatan bimbingan, pengajaran atau latihan bagi peranya dimasa mendatang. Agar dapat meningkatkan kualitas suatu bangsa dapat dilihat dari peningkatan mutu pendidikan. Penelitian ini bertujuan untuk meningkatkan hasil belajar siswa dengan mengunakan model pembelajaran blended learning pada mata pelajaran komputer dan jaringan dasar di SMK Negeri 2 Maluku Tenggara. Jenis pnelitian ini mengunakan penelitian tindakan kelas (PTK) Model Lewin Men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…In previous research, it was found that blended learning had an effect on the learning outcomes of PAI, mathematics, history, computers and basic networks (Firmansyah, 2020;Kiranawati, 2016;Marhendra et al, 2016;Putra, 2015;Tethool et al, 2021). In this study, it will be known the effect of blended learning on the learning outcomes of junior high school students in Integrated Social Sciences material.…”
Section: Introductionmentioning
confidence: 77%
“…In previous research, it was found that blended learning had an effect on the learning outcomes of PAI, mathematics, history, computers and basic networks (Firmansyah, 2020;Kiranawati, 2016;Marhendra et al, 2016;Putra, 2015;Tethool et al, 2021). In this study, it will be known the effect of blended learning on the learning outcomes of junior high school students in Integrated Social Sciences material.…”
Section: Introductionmentioning
confidence: 77%
“…Sebagai salah satu indikator keberhasilan, maka tentu prestasi belajar sangat penting baik kepada guru maupun kepada siswa. Kepada guru, prestasi belajar digunakan sebagai patokan untuk mengukur keberhasilan guru dalam mengajar (Tethool et al, 2021). Sementara kepada siswa, prestasi belajar berguna sebagai data untuk menilai serta mengukur derajat kemampuan dan pencapaian setelah mengikuti pembelajaran terlepas dari apakah mengalami perubahan positif atau perubahan negatif.…”
Section: Pendahuluanunclassified
“…Barriers to online learning can arise due to educators' and students' limitations and constraints on the learning support tools used (Pusung et al, 2021;Sandre et al, 2021;Tethool et al, 2021). In addition to problems with supporting infrastructure, online learning problems also occur due to the lack of teacher competence in designing and managing interactive online learning (Sabaniah et al, 2021;Suprapmanto & Utomo, 2021;Warsito et al, 2022).…”
Section: Introductionmentioning
confidence: 99%